Parathyroid hormone receptor 1 gene knockdown induces aortic occlusion in zebrafish embryos. (22nd September 2015) - Lees, JC; Crossman, DC; Chico, TJA
Abstract : Introduction: Mutations in parathyroid hormone receptor 1 (PTH1R) are responsible for Blomstrand's chondrodysplasia. This fatal bone disorder is associated in some cases with aortic coarctation. However, mouse PTH1R knockouts die as a result of cardiovascular defects but do not display aortic coarctation, suggesting that PTH1R does not contribute to aortic formation. We therefore determined the effect of morpholino antisense knockdown of PTH1R on vascular development in transgenic zebrafish embryos that allow detailed serial imaging of embryonic vascular development. Methods and Results: Morpholino antisense oligonucleotides (MO) were designed either totally to prevent PTH1R messenger RNA transcription or induce aberrant splicing. When injected into one-cell embryos, the splice blocking MO truncated PTH1R mRNA, by approximately 100 bp compared with wild type. The abnormally spliced mRNA persisted until at least 3 days post-fertilisation, by which point the aorta, cardinal vein and intersomitic vessels are well formed. When either the start blocking or splice blocking morpholino was injected into transgenic embryos expressing green fluorescent protein in either the endothelial cytoplasm or localised to endothelial nuclei, we observed a total occlusion of the mid-distal aorta in 36 ± 16% of PTH1R morphants (of 153 embryos) at 2 days post-fertilisation. In other morphants we observed a variable degree of reduced blood flow in the distal aorta suggestive of partial aortic occlusion. Aortic occlusion was accompanied by the diversion of blood flow into the intersegmental vessels proximal to the occlusion, which subsequently loop to join the caudal vein. The fig shows representative 3D reconstructions of confocal micrographs obtained from control and PTH1R morphant embryos at 2 days post-fertilisation. The phenotype of an occluded aorta diminished over time; by 5 days post-fertilisation this was seen in only 2 ± 2% of embryos, suggesting that as PTH1R mRNA splicing recovered from the MO, the embryo can repair the occlusion through innate mechanisms. Conclusion: We conclude that PTH1R is responsible for the correct patterning of the aorta, and reducing translation of PTH1R mRNA is associated with localised defects in aortic patterning analogous to aortic coarctation. This supports the suggestion that aortic coarctation associated with Blomstrand's chondrodysplasia is directly attributable to PTH1R mutation. Our findings suggest that the mechanisms of aortic construction are conserved between humans and zebrafish, and that the zebrafish is therefore a useful model with which to examine the genetic contribution to congential vascular malformations.